Merangka strategi pembangunan mapan komuniti orang asli: suatu penilaian tahap kemapanan komuniti Temiar di Rancangan Pengumpulan Semula (RPS) Legap & Pos Kuala Mu, Daerah Kuala Kangsar, Perak - Kamarudin, Khairul Hisyam (2005)
In the declaration of the Conference on Environment and Development at Rio de Janeiro 1992, the role of indigenous people in environmental management and development for achieving sustainability was recognized because of their knowledge and traditional practice. However, the value and traditional practices of the indigenous communities today has gradually disappear due to pressure from modernization and influence of market economy which penetrated them. The study examine the extent to which the knowledge and practice of the Orang Asli community comply with sustainable development principles and how their knowledge and practice could be used to derive a framework for sustainable development strategies of Orang Asli community. Based on a case study of Orang Asli communities of Kampung Perjek and Kuala Mu, this study evaluate the level of sustainability of the communities on the basis of indicators formulated. 45 indicators were finalized in comprehensive manned covering economic, social and physical dimensions. These indicators then were categorized into attitude, system and situational components. Fieldworks were conducted about 28 days to make observations, household survey and in-depth interviews of selected respondents. The level of sustainability of each indicator was analyzed based on information collected and index was used to measure overall sustainability. This study shows variability of sustainability levels of each indicators. Levels of sustainability were moderate for the attitude and situation indicators and low for the system indicators. On the basis of the findings and the brainstorming process with the locals, this study suggests a framework for the sustainable development strategy of Orang Asli community which includes commercialization of organic farming, tourism, human resource development, rearrangement of settlement and environmental management.